PREVALENCE OF BURNOUT SYMPTOMS IN NURSES HOSPITAL ASSIGNED TO COVID-19 ISOLATION ROOMS - Sylvia Jessy Kurniawan; Kuswantoro Rusca Putra; I Gusti Agung Gede Utara Hartawan (Universitas Airlangga, 2022)
Background: Burnout is a health problem that may happen to nurses and may impact patient safety and organization in any situations, especially during the second wave of COVID-19 pandemic. Aims: This study aimed to identify the prevalence of burnout among nurses in charge of isolation rooms and its relationship to their demographics factor. Methods: This research design is descriptive-analytic quantitative and cross-sectional. It involved 124 nurses assigned to isolation rooms for COVID-19 patients admitted to the first referral hospital in Bali. Data were collected using a questionnaire adopted from the Maslach Burnout Inventory to identify burnout symptoms. Demographic questionnaire was administered to garner respondents' demographics. Results: High category of burnout was related to emotional exhaustion found in 66.1% of the respondents, depersonalization in 33.1%, and reduced personal accomplishment in 0.8%. Age, marital status, education, and gender were not related to burnout. Nurses who worked in non-ICU experienced higher burnout than ICU (p < 0.05). Conclusions: The prevalence of burnout symptoms in the nurses who were in charge in COVID-19 isolation rooms is in the high category. Hospital management must consider demographic factors to improve the work environment, recruit new employees, conduct routine health checks, and provide mental health treatments consistently.